PENEGAKAN HUKUM TERHADAP PELAKU PENYIMPANGAN SEKSUAL DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Situmeang, Sahat Maruli Tua; Putri, Latiffa Rojikin; Mendisa, Karlina (Lembaga Marwah Rakyat, 2023)
The LGBT phenomenon has pros and cons so it has become a controversial topic of conversation among society. LGBT began to appear in society more or less in the 1990s. The presence of the LGBT community which is contrary to religious values and life is rampant in various levels of society, therefore special treatment is needed to regulate LGBT matters so that the role of the community is needed. This research aims to find out the regulations and their enforcement regarding LGBT behavior in Indonesia and the problems faced. This research method uses normative juridical research methods. Based on law enforcement, the provisions regarding adults molesting minors are contained in Article 292 of the Criminal Code which regulates intimate relationships between individuals of the same sex. In implementation, it is necessary to reform the law which regulates more specifically the age group of LGBT perpetrators. Efforts that can be used as a response tool include providing guidance to gay party perpetrators, apart from that, support from various parties is needed to achieve success in response